2018
DOI: 10.1159/000491828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-Hypertensive Medication History on Arteriovenous Fistula Maturation Outcomes

Abstract: Background: The arteriovenous fistula (AVF) is the preferred vascular access for hemodialysis. However, approximately half of AVFs fail to mature. The use of angiotensin converting enzyme inhibitors (ACE-Is), angiotensin receptor blockers (ARBs), and calcium channel blockers (CCBs) exerts favorable endothelial effects and may promote AVF maturation. We tested associations of ACE-I and ARBs, CCBs, beta-blockers, and diuretics with the maturation of newly created AVFs. Methods: We evaluated 602 participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Despite the small number of participants, the overall proportion of participants with functional maturation at 180 days ± 4 weeks after surgery was 46% and is similar to other trials or registries (~45%-60%). 2,23,24 In the US Renal Data System, 25 the median time to first use of matured AVF is 108 days-similar to our results of the six participants with functional AVF maturation within 180 days at 48, 76, 77, 84, 96, and 145 days.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the small number of participants, the overall proportion of participants with functional maturation at 180 days ± 4 weeks after surgery was 46% and is similar to other trials or registries (~45%-60%). 2,23,24 In the US Renal Data System, 25 the median time to first use of matured AVF is 108 days-similar to our results of the six participants with functional AVF maturation within 180 days at 48, 76, 77, 84, 96, and 145 days.…”
Section: Discussionsupporting
confidence: 81%
“…This hypothesis was tested in the Hemodialysis Fistula Maturation Study, which included 602 patients on hemodialysis via AVF. However, the study showed that angiotensin I converting enzyme inhibitor and angiotensin II receptor blocker were not associated with improved AVF patency 33 . Consistent with this study, our findings also showed that angiotensin inhibitors were not associated with AVF patency.…”
Section: Discussionmentioning
confidence: 85%
“…Wang et al analyzed the data from a prospective multicenter cohort in the United States and included 602 patients with newly created AVFs. 11 They compared the access maturation according to various antihypertensive medications and revealed that calcium channel blockades resulted in better overall AVF maturation than other medications. However, the use of RASBs was not associated with AVF maturation.…”
Section: Discussionmentioning
confidence: 99%
“…As RASBs have such effects on blood vessels, they may have beneficial effects in vascular access‐related outcomes in patients on HD. However, results on the association between the use of RASBs and vascular access‐related outcomes are inconsistent, and further studies are needed to confirm the usefulness of RASBs 9–13 . Thus, we aimed to compare vascular access‐related outcomes according to the use of RASBs using a representative sample of patients on maintenance HD.…”
Section: Introductionmentioning
confidence: 99%